(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
In this article, we explore the relationship between different languages, namely Russian and Uzbek. The methodological approach is based on a comparative analysis of vocabulary, grammar and phonetics. The results of the study showed that the Uzbek language has a large number of borrowings from the Russian language, which is associated with historical factors and modern political and economic ties between the two countries.